Narrating codex history: the case study of a psalter-hymnal from Alcobaça Monastery, Portugal - Casanova, Conceição (2022)
This article provides the first in-depth study of historic content and materials used in the production of a liturgical codex from the collection of manuscripts of the Monastery of Alcobaça: the Psalter-hymnal (Lisbon, National Library, Alc. 11). To answer provenance questions and trace the manuscript’s history, a multidisciplinary team studied the entire procedure of making the codex, which went from in-depth textual, liturgical, and codicological analyses, to examining material composition and bookbinding methods with complementary analytical techniques. The team was able to track the manuscript’s historical trajectory through successive additions and interventions/alterations. Interpretation of the historic information and the resulting technical data confirmed the belief that this is a twelfth-century manuscript produced in the scriptorium of Alcobaça and underlined the role that the manuscript played in this Cistercian monastery during the Middle Ages, and possibly throughout the following centuries. This led the team to approach the codex’s “cultural significance” and perceive later alterations and interventions as evidence of the monks’ intensive use of this manuscript and the great care they took to preserve their monastic library. The new data and knowledge acquired about this precious codex proved to be fundamental for future digital access policy definition and the conservation making decision